Optimization of Vulvovaginal Candidiasis Induction in Rattus norvegicus using Estradiol Benzoate: A Preliminary Study - Dariatul Janah; Andi Yasmon; Ibnu Agus Ariyanto (Biomedical Journal of Indonesia, 2026)
Introduction. Approximately 75% of women of reproductive age have opportunistic vaginal infection with Candida albicans at least once in their lifetime, which is known as vulvovaginal candidiasis (VVC). The increasing global prevalence and emergence of antifungal agents underscore the importance of research into effective prevention and treatment. In vivo studies using rats are commonly conducted, as they provide valuable knowledge on reproductive diseases in humans such as VVC. Methods. Pseudoestrus was induced in wistar rats by subcutaneous injection of estradiol benzoate at doses of 0.1 and 0.2 mg/rat/week. Cytologic observation using vaginal smear staining is used to detect cornified epithelial cells and leukocytes. VVC was induced by intravaginal administration of Candida albicans ATCC10231 (0.5 and 1.0 McFarland) daily for 5 consecutive days. VVC confirmation by microscopic detection of Candida albicans pseudohyphae from vaginal swabs, supported by viability testing of vaginal lavage cultures. Results. Pseudoestrus induction was optimal at a dose of 0.2 mg/rat/week, as both animals were maintained in this phase for 3 consecutive days. Furthermore, an inoculum of 1.3×107 CFU/mL (McFarland standard 1.0) administered for 5 days successfully induced VVC in both animals. Microscopic confirmation revealed intracellular pseudohyphae, supported by the growth of viable Candida albicans from vaginal lavage cultures. Conclusion. The optimal estradiol benzoate protocol for pseudoestrus induction was 0.2 mg/rat/week, and pseudoestrus was maintained for 3 days without ovariectomy. The optimal VVC rat model was established using intravaginal Candida albicans at 1.3×107 CFU/mL for 5 days, with viability from lavage cultures of 1.3×102 CFU/mL and 0.3×102 CFU/mL.